Gender dysphoria/gender incongruence of pre or post-pubertal onset: differences in psychiatric comorbidities and socio-familial determinants. A cross-sectional study - Marta P. Antunes; Ana F. Lopes; Pedro Carvalho-; Otília Queirós; João Guerra; Cláudia Falco; Dulce Soeiro (Publicaciones Permanyer, 2023)
Introduction: The increase in the number of adolescents referred to specialized gender identity clinics generated an international phenomenon, that has also been experienced at the Outpatient Adolescence Service of Departamento de Pedopsiquiatria e Saúde Mental da Infância e Adolescência, Centro Hospitalar Universitário do Porto. Objective: To assess whether there are differences in psychiatric co-morbidities and other socio-familial determinants in pre- or post-pubertal-onset of Gender Dysphoria/Gender Incongruence. Methods: Selection of a convenience sample of adolescents assessed for Gender Dysphoria/Gender Incongruity at the Outpatient Adolescence Service of Departamento de Pedopsiquiatria e Saúde Mental da Infância e Adolescência, Centro Hospitalar Universitário do Porto, from January 2018 to December 2021 that was divided into two groups: pre- and post-pubertal onset. Data were analyzed with SPSS, version 26. Results: Forty-one adolescents with cross-gender behaviors, 28 (68.3%) females, and 13 (31.7%) males were included. Pre-pubertal cross-gender behavior was observed in 21 (51.2%) adolescents. The prevalence of psychiatric co-morbidities was 65.9% and the prevalence of social-family risk factors was 63.4%, without statistical significant differences between the two subgroups. Discussion: The small sample is an important limitation. Even so, results are in line with the literature, concerning the increasing number of birth-designated females presenting for care. However, there were no differences in this sample, so it is not possible to infer differences between the two subgroups regarding the compared parameters. We consider essential further studies to better understand this phenomenon and its particularities at a stage of development that is in itself turbulent.